Sophie Scholl : [videorecording (DVD)] : die letzten Tage - Rothemund, Marc, 1968-; Jentsch, Julia, 1978-; Hinrichs, Fabian (Zeitgeist Films, 2005)
"The film depicts the last six days (February 17-22, 1943) in the life of Sophie Scholl from her own perspective: that of a courageous and vibrant young woman who is willing to face death for her belief in her ideals and those of the White Rose, an underground resistance movement to which she belongs. Through their resistance and protest against the Nazi regime, Sophie and her fellow members of the White Rose become synonymous with civil courage and a peaceful struggle against the rule of violence and oppression."--Container.